Analysis of Health Literacy Index Difference Amongst Generation in Jagapura Primary Healthcare Work Area - Maitsa' Fatharani; Nafiys Hilmy (Faculty of Medicine, University of Jember, 2023)
Health literacy is one of the factors which has a big contribution to a person's health status. The rapidity of technology growth eases access to health information, this situation has to be balanced with good health literacy index. Several factors as generation, occupation, and education influence health literacy index. Many measuring tools have been developed to assess the health literacy index. Researcher uses the latest health literacy survey questionnaire in Indonesia, namely HLS-EU-SQ10-IDN which contains 10 questions. This type of research is analytic observational. The research was conducted in the work area of ​​the Jagapura Primary Health Care, Gegesik District, Cirebon Regency, West Java. A total of 146 people that spread over five village is taken as samples with purposive sampling method. The results of Chi Square analysis is the association between generation and health literacy index showed insignificant results with p = 0.705. For the correlation with work, the results are also insignificant with p = 0.296. Meanwhile, education level is associated significantly with p = 0.018. The data obtained indicate that there is no significant correlation between generational differences and the health literacy index. Older generation with higher educational background tends to have better health literacy index. On the other hand, the researcher concludes that government need a strategy to increase the quantity and quality of education in Indonesia as an endeavour to increase health literacy index in our society. Keywords: health literacy index, generation, education, occupation